The River Exists, Therefore I Am: Ecocriticism, Nature and Human Nature in Willa Cather’s 'The Enchanted Bluff' - Sardari, Alireza (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2020)
Today, environmental degradation and nature preservation are among the most discussed topics in media, academia, and beyond. Adopting Glotfelty’s ecocritical approach, this article investigates the relationship between human culture and the natural world in Willa Cather’s The Enchanted Bluff (2009). The present study determines the different representations of nature along with the ecological issues to (a) heighten the ecological awareness and (b) to provide a fresh perspective to look at the natural world; therefore, this article shifted its focus from the anthropocentric attitude to the biocentric and focuses on nature and its correlation with humanity. This paper challenges the human/nature binary to help us look at the natural world stripped of established stereotypes. The results indicate that nature is an indivisible portion of human identity; furthermore, humankind and the natural world are codependent and interconnected; the results also emphasize that preserving the natural world is, indeed, the prerequisite for the protection of humanity.